Research on the Development of Photovoltaic Solar Greenhouse in Western China from the Perspective of Continuous Enrichment - Li, Jiang (International Journal of Management and Education in Human Development, 2023)
As one of the new energies, photovoltaic solar energy has four advantages compared with traditional energy: huge reserves, convenient application, durable supply, clean and harmless. With the progress of science and technology, the development of photovoltaic solar energy industry is extremely rapid. In the foreseeable future, photovoltaic solar energy will become an effective alternative to the depleted traditional fossil energy sources. In this context, the world's photovoltaic solar energy industry has entered a golden period of development. At present in the world, the use of photovoltaic solar energy is mainly concentrated in the field of solar power generation. Achieve sustainable development through rational use of natural resources. By collecting and sorting out the literature of photovoltaic solar energy industrial policy, this paper concludes that the research of domestic and foreign experts on photovoltaic solar energy industrial policy mainly focuses on two aspects: on the one hand, the research on the development of photovoltaic solar energy industrial policy; on the other hand, the interpretation of photovoltaic solar energy future development by the photovoltaic industrial policy promulgated and implemented by various countries. Through research, this paper finds that existing literature studies on the development of photovoltaic solar energy industry mainly focus on the forms, functions and industrial policies of photovoltaic solar energy in the sustainable development of energy, and needs to be strengthened in the following three aspects: First, the application of photovoltaic solar energy in modern agriculture is relatively less, more concentrated in photovoltaic solar power generation and the development of photovoltaic industry chain and related policy research fields; Second, there is still room for development in the research of photovoltaic solar energy on economic stimulation in remote areas. Existing research focuses on photovoltaic solar lighting in remote areas. There is a lack of research on the economic driving effect of large-scale photovoltaic solar energy in remote areas. Third, the current photovoltaic solar energy construction mode is the enterprise-led enterprise dividend sharing mode. The government, farmers and state-owned enterprises jointly participate in the PV solar power generation project mode, the evaluation of state-owned enterprises' social responsibility, and the conversion of cash transfer profit into technical support are few relevant studies. This study can be used as a starting point to conduct a feasibility study on large-scale construction of PV solar greenhouse in the arid and rainless regions of western China, so as to provide a sustainable way for farmers to get rich.